Burden and predictors of M-pox suspected cases in a rural setting of Cameroon: implications for developing countries - Nganmegni, Flaure Rasana P; Ngo, Julienne Louise L; Essomba, René G; Nguwoh, Philippe S; Metomb, Franck S; Epee, Emilienne; Mandeng, Nadia; Mballa, Georges-Alain E; Boum II, Yap; Okomo, Marie Claire A; Taheu, Christian N; Fokam, Joseph (The Journal of Infection in Developing Countries, 2024)
Introduction: M-pox is a re-emerging pathogen that is spreading rapidly in developing countries, presenting a serious health risk. Data are scarce on M-pox and its determinants in endemic countries such as Cameroon. This study aimed to assess the epidemiological burden and factors linked to the resurgence of M-pox in high-risk communities in Cameroon. Methodology: A community-based surveillance was conducted from April to October 2022, among 88 individuals at the Ayos Health District (AHD). Participants were interviewed, and cases of M-pox were defined based on World Health Organization (WHO) clinical criteria. Data were analyzed using CSPro v.6.0 and SPSS v.20.0, with p < 0.05 as the statistical significance level. Results: The overall suspected M-pox cases rate was 25% (22/88). Following logistic regression, history of chickenpox (OR 0.14, p = 0.05); history of smallpox (OR 9.14, p < 0.001), vaccination against poxviruses (p < 0.001), skin infection (OR 210, p < 0.001), upper respiratory infection (p < 0.001), atypical dermatitis (OR 144, p < 0.001), skin allergy (OR 68.57, p < 0.001), contact with an individual suffering from M-pox in the last 14 days before symptoms onset (OR 9.14, p < 0.001), contact with animals in the last 14 days before symptom onset (OR 12.68, p  0.001), regular meal consumption (OR 0.35, p = 0.04), meal-sharing, and handling of bushmeat (p = 0.01) were significantly associated with M-pox infection. Conclusions: The clinical features of M-pox were common in rural Cameroonian setting, suggesting the need for active surveillance in these high-risk communities.